German Chancellor Angela Merkel's visit to ILRI July 2011 - International Livestock Research Institute (International Livestock Research Institute, 2011)
Speeches by ILRI Director General Carlos Seré and Chancellor Angela Merkel of the Federal Republic of Germany on her visit to the ILRI Nairobi campus on 12 July 2011. Language: German and English